A Dominant Heterozygous Mutation in COG4 Causes Saul–Wilson Syndrome, a Primordial Dwarfism, and Disrupts Zebrafish Development via Wnt Signaling - Xia, Zhi-Jie; Zeng, Xin-Xin I.; Tambe, Mitali; Ng, Bobby G.; Dong, P. Duc S.; Freeze, Hudson H. (Frontiers in Cell and Developmental Biology, 2021)
Saul-Wilson syndrome (SWS) is a rare, skeletal dysplasia with progeroid appearance and primordial dwarfism. It is caused by a heterozygous, dominant variant (p.G516R) in COG4, a subunit of the Conserved Oligomeric Golgi (COG) complex involved in intracellular vesicular transport. Our previous work has shown the intracellular disturbances caused by this mutation; however, the pathological mechanism of SWS needs further investigation. We sought to understand the molecular mechanism of specific aspects of the SWS phenotype by analyzing SWS-derived fibroblasts and zebrafish embryos expressing this dominant variant. SWS fibroblasts accumulate glypicans, a group of heparan sulfate proteoglycans (HSPGs) critical for growth and bone development through multiple signaling pathways. Consistently, we find that glypicans are increased in zebrafish embryos expressing the COG4p.G516R variant. These animals show phenotypes consistent with convergent extension (CE) defects during gastrulation, shortened body length, and malformed jaw cartilage chondrocyte intercalation at larval stages. Since non-canonical Wnt signaling was shown in zebrafish to be related to the regulation of these processes by Glypican 4, we assessed wnt levels and found a selective increase of wnt4 transcripts in the presence of COG4p.G516R. Moreover, overexpression of wnt4 mRNA phenocopies these developmental defects. LGK974, an inhibitor of Wnt signaling corrects the shortened body length at low concentrations but amplifies it at slightly higher concentrations. WNT4 and the non-canonical Wnt signaling component phospho-JNK are also elevated in cultured SWS-derived fibroblasts. Similar results from SWS cell lines and zebrafish point to altered non-canonical Wnt signaling as one possible mechanism underlying SWS pathology.